Attenuating effects of pentoxifylline on memory, oxidative stress and monoamine levels in the hippocampus of seizure induced mice. - Ahmad, Mohammad; Abu-Taweel, Gasem M. (JOURNAL OF ADVANCES IN BIOLOGY, 2014)
Lithium pilocarpine (Li-Pc) - induced seizures in rodents serve as convenient animal models to study the mechanisms of epileptogenesis particularly with reference to the development of status epilepticus (SE), memory retention, neurotransmitters and oxidative stress systems in the brain hippocampus which may be involved in the modulation of SE. In the present study, adult male mice were used to study the neuroprotective effects of pentoxifylline (PTX) against Li Pc induced SE